Impact the field of athletics in the development of Fitness for ages 11-12 years - Talaat, Firas (Journal of Physical Education, 2012)
Works athletics for children in the development of motor skills different and one of these capabilities Fitness, which is one of the important elements in the link between motor abilities of different any where there is a consensus between the capacity led to the harmony of movement are distinct, hence the importance of research in the preparation of the field of the proposal can be which develop the capacity of Fitness for the kids, and the research aims to prepare the field of developmental athletics for children ages 11-12 years, and I have to use the researcher the experimental method on a sample of elementary school students for the year Aldarcy 2011-2012 and the 24 students, has formed a percentage of the sample (7.25 %) of the total, and emerged through the results of research show that the preparation of the field and divided into areas and helped limit the contests in which the research sample in the development of some physical abilities, the researcher recommends the preparation of the fields, especially in athletics of all primary schools across the country .